The Impact of Reflexive and Empathic Abilities on Developing the Professional Competence of a Teacher - T A Shilova; G V Kharitonova (Peoples' Friendship University of Russia (RUDN University), 2015)
The article presents a study of the effect of reflexive and empathic abilities on the development of the professional competence of a teacher. The concept of models of psychological features of reflection and empathy is considered. The influence of reflection and empathy on the formation of professional competence is revealed. The ways of the development of reflection and empathy are shown.